Retrospective analysis of capecitabine and oxaliplatin (XELOX) plus bevacizumab as a first-line treatment for Japanese patients with metastatic colorectal cancer - UCHIMA, YASUTAKE (D.A. Spandidos, 2014)
XELOX plus bevacizumab is an effective treatment strategy and has a manageable tolerability profile when administered to Japanese patients with metastatic colorectal cancer (mCRC). In this study, we retrospectively reviewed cases in which XELOX plus bevacizumab were administered in order to evaluate its efficacy and safety in clinical practice. In total, 40 patients with mCRC who presented at Fuchu Hospital received XELOX plus bevacizumab as a first-line treatment between September, 2009 and April, 2012. Eligible patients had histologically confirmed mCRC. XELOX consisted of a 2-h intravenous infusion of oxaliplatin 130 mg/m(2) on day 1 plus oral capecitabine 1,000 mg/m(2) twice daily for 2 weeks of a 3-week cycle. Overall survival (OS) and survival benefit were analyzed when patients continued with XELOX plus bevacizumab beyond disease progression. The median progression-free survival (PFS) was 290 days [95% confidence interval (CI): 222–409 days] and the median OS was 816 days (95% CI: 490 days-not calculated). The response rate (RR; complete plus partial response) was 67.5%, and the disease control rate (RR plus stable disease) was 90%. The most common adverse events observed following administration of XELOX plus bevacizumab were neurosensory toxicity (82.5%), anorexia (50%), hypertension (45%) and a decrease in the platelet count (40%). The most common grade 3/4 adverse events were neurosensory toxicity (15%) and fatigue (15%). In conclusion, XELOX plus bevacizumab may be considered a routine first-line treatment option for patients with mCRC. Notably, the combination of capecitabine and bevacizumab was safe with an acceptable toxicity profile and induced a significant rate of disease control.